Pentingnya Literasi Informasi Dan Komunikasi di Era Digital - Luthfiah Anwar, Wan Tasya; Nasution, Wahyuddin Nur; Padli Nasution, Muhammad Irwan (Innovative: Journal Of Social Science Research, 2025)
The digital era has brought major changes in various aspects of life, especially in the field of information and communication. Digital literacy is crucial to equip individuals with the ability to filter, understand, and use information wisely. This paper discusses the importance of information and communication literacy in supporting the effective use of digital technology, fostering creativity, building productive communication, and playing an active role in global society. Through a literature study approach, this article describes the use of digital technology in education, communication, and the formation of ethical digital citizenship.